Addressing agriculture in climate change negotiations: A scoping report - Campbell, Bruce M.; Mann W; Melendez-Ortiz R; Streck, C.; Tennigkeit, Timm (Meridian Institute, 2011)
This Report was developed in the context of the “Global Dialogue on Climate Change and Agriculture,” a project facilitated by the Meridian Institute that began in August 2010. The Meridian Institute is an internationally recognized, nonprofit organization that facilitates neutral and independent policy dialogues and assessments. The Global Dialogue is a program intended to provide relevant information and opportunities for productive engagement and discussion among government negotiators, experts, stakeholders, and others involved and interested in climate change and agriculture. For this report, the Institute convened a team of international, independent expert authors, and facilitated the work of the author team as well as a series of informal dialogues with a broad range of country negotiators, nongovernmental organizations, and agricultural experts. The report is intended to provide context and analysis for addressing agriculture in international climate negotiations with the aim of helping to inform climate negotiators and other stakeholders by identifying options and unpacking issues of interest; and not to express opinions or be prescriptive. To achieve this objective, the report was guided by an iterative process comprised of dozens of individual interviews from August to December 2010, and two in-person group consultations convened February 15-17, 2011 in Johannesburg, South Africa, and April 11-13, 2011, in Bangkok, Thailand.